The Impementation of Classpoint as an Interactive Media to Increase Students’ Interest in Learning Arabic at Grade VII.4 of MTsN 2 Makassar - Anugrahyarti, Nurul; Beddu Malla, Agussalim; Wahab, Abdul; Zainal, Abdul Qahar; Hasriani, Andi (Journal of Digital Arabic Language Education, 2025)
This study aims to determine the application of Classpoint interactive learning media in increasing the interest of VII.4 students in learing Arabic at MTsN 2 Makassar. This research employed a Classroom Action Research (CAR) design conducted in two cyles (Kemmis & McTaggart model) through the stages of planning, action, observation, and reflection. The subjects of this study consisted of 38 students. The instruments used included a learning interest questionnaire (15 items, 4-point scale), teacher implementation observation sheets, student activity observation sheets, and documentation. The results showed a significant improvement in students’ learning interest from the pre-cycle to the second cycle. In the pre-cycle, the average score was 30.58 (50.96%, low category). After the implementation of Classpoint in the first cycle, the average score increased to 43.73 (72.89%, moderate category), with 27 students (71.05%) in the high category and 11 students (28.95%) in the moderate category. In the second cycle, there was a further increase to an average of 57.34 (95.57%, high category), with all 38 students (100%) classified in the high category. Based on these findings, it can be concluded that the use of Classpoint interactive learning media is effective in increasing students’ interest in learning Arabic at grade VII.4 of MTsN 2 Makassar. It is recommended that teachers utilize Classpoint in a structured manner and provide assistance for students who are less familiar with digital devices to ensure more equitable outcomes.